PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TIME TOKEN TERHADAP HASIL BELAJAR SISWA KELAS III SD - Setia Hartaty Saragih; Juliana; Bogor Lumbanraja; Reflina Sinaga; Ester Julinda Simarmata; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to improve student learning outcomes, to determine the process of implementing student learning by using the Time Token Type Cooperativ learning model, to determine the effect of the Time Token Type Cooperative learning model on student learning outcomes on theme I growth and development of living things SD Negeri 013823 Teluk Dalam class III in the 2024/2025 school year. Thepopulation is all third grade students totaling 30 students. The sample was taken by Simple saturated. third grade students of SD Negeri 013823 Learning Year 2024/2025, namely 30 students. The method used in this research is the experimental method. The experimental method used in this study is to seek the effect of certain treatments on others under controlled conditions. Based on the results of statistical processing, it shows that learning outcomes using the Time Token Type Cooperative learning model are in the good category with an average of 79. While learning outcomes without using the Time Token Type Cooperative learning model have not really met the KKTP that has been applied with an average of 55. By using the tcount = 13,870 test while ttable= 2.042 because tcount ≥ ttable then Ho is rejected and Ha is accepted. This proves that there is a significant influence between the Time Token Type Cooperative learning model on the learning outcomes of third grade students of SD Negeri 013823 Teluk Dalam Learning Year 2023/2024.